Risk factors, awareness of disease and use of medications in a deprived population: differences between indigent natives and undocumented migrants in Italy. (8th November 2019) - Fiorini, Gianfrancesco; Cerri, Cesare; Magri, Flavia; Chiovato, Luca; Croce, Laura; Rigamonti, Antonello E; Sartorio, Alessandro; Cella, Silvano G
Abstract: Background: Undocumented migrants experience many health problems; a comparison with a suitable control group of natives living in the same socio-economic conditions is still lacking. Methods: Demographic data and data on risk factors, chronic conditions and dietary habits were obtained for 6933 adults (2950 Italians and 3983 undocumented migrants) receiving medical assistance from 40 non-governmental organizations all over the country. Results: Attributed to the fact that these were unselected groups, differences were found in their demographic features, the main ones being their marital status (singles: 50.5% among Italians and 42.8% among migrants; P < 0.001). Smokers were more frequent among Italians (45.3% versus 42.7% P = 0.03); the same happened with hypertension (40.5% versus 34.5% P < 0.001). Migrants were more often overweight (44.1% versus 40.5% P < 0.001) and reporting a chronic condition (20.2% versus 14.4% P < 0.001). Among those on medications ( n = 1354), Italians were fewer ( n = 425) and on different medications. Differences emerged also in dietary habits. Conclusions: Differences in health conditions exist between native-borns and undocumented migrants, not because of a bias related to socio-economic conditions. Further studies are needed to design sustainable health policies and tailored prevention plans.